Randomly Correlated Data - Copertari, Luis F.; Reyna-Barajas, Gloria V.; Lozano-Razo, Georgina; Zavala-Rayas, Javier (Advances in Social Sciences Research Journal, 2026)
The random correlation data algorithm allows the creation of two randomly correlated variables having a relatively strong positive or negative correlation between them. We have used this algorithm in project management and, more specifically, in project portfolio selection. This paper describes the most important concepts and portrays the relevant equations for the algorithm being considered. The equations can be applied to other domains of inquiry. Also, although the random distribution generator was uniformly distributed, other random generators can be used, such as normally distributed random generators.